Analysis of phenol production technology from the waste of empty palm oil bunches: A review of methods and process efficiency - Adi Saputro Erwan; Bahari Alias Azil; Dwi Nurherdiana Silvana; Saraswati Rahaju; Ariyanti Dessy; Roriza Putri Redina Erda; Febrila Awardani Niken (E3S Web of Conferences)
Empty palm oil bunches (EPB) are waste from the oil palm farming process that has not been widely utilized. This waste can be used as a raw material for the manufacture of phenols. There are various processes in making phenol from empty palm oil bunch waste, including pyrolysis and hydrothermal liquefaction. Pyrolysis is the process of decomposition of a material that occurs at high temperature, which produces three products, bio-oil, bio-char, and gas. The phenol content contained in bio-oil is taken using a liquid-liquid extraction process. This pyrolysis has advantage including compactness and relative simplicity, fuel flexibility and clean carbon by product and low CO and CO2 emissions. This literature study aims to explain the method of making phenol and become a reference in terms of the selection of the process in making phenol, especially from empty palm oil bunches.